sRAGE and Risk of Diabetes, Cardiovascular Disease, and Death - Selvin, Elizabeth; Halushka, Marc K.; Rawlings, Andreea M.; Hoogeveen, Ron C.; Ballantyne, Christie M.; Coresh, Josef; Astor, Brad C. (Diabetes (New York, N.Y.), 2013)
Advanced glycation end products (AGEs) and their receptors are strongly implicated in the development of diabetes complications. When stimulated by AGEs, the receptors for AGEs (RAGEs) induce inflammation and are thought to fuel disease progression. Soluble circulating RAGE (sRAGE) may counteract the detrimental effects of RAGE. We measured sRAGE in stored plasma from a random sample of 1,201 participants in the Atherosclerosis Risk in Communities (ARIC) Study who were aged 47–68 years, had normal kidney function, and had no history of cardiovascular disease. In cross-sectional analyses, black race, male sex, higher BMI, and higher C-reactive protein were independently associated with low sRAGE. The racial difference was striking, with blacks approximately three times more likely to have low sRAGE compared with whites even after adjustment. During ~18 years of follow-up, there were 192 incident coronary heart disease events, 53 ischemic strokes, 213 deaths, and 253 cases of diabetes (among the 1,057 persons without diabetes at baseline). In multivariable Cox models comparing risk in the first quartile with that in the fourth quartile of baseline sRAGE, low levels of sRAGE were significantly associated with risk of diabetes (hazard ratio 1.64 [95% CI 1.10–2.44]), coronary heart disease (1.82 [1.17–2.84]), and mortality (1.72 [1.11–2.64]) but not ischemic stroke (0.78 [0.34–1.79]). In conclusion, we found that low levels of sRAGE were a marker of future chronic disease risk and mortality in the community and may represent an inflammatory state. Racial differences in sRAGE deserve further examination.